Deflationary Truth, Ordinary Truth and Relative Truth - Caso, Ramiro (Daimon Revista Internacional de Filosofia, 2023)
Horwich (Mind 123(491), 2014) has argued that only someone with inflationary tendencies could feel inclined to endorse truth relativism. In doing so, he argues that deflationism about truth entails the denial of relativism. If sound, Horwich’s argument could entail that truth relativism is incompatible with any conception of our ordinary truth predicate according to which there is some sort of equivalence between a ground-language claim that p and the corresponding claim that p is true. Arguably, any story the relativist might give about our ordinary truth predicate, it should entail some such equivalence. Hence, there is a problem for truth relativism that needs to be addressed.